The Analysis of Abstraction Personification in Skillet’s Selected Song - Putu Devi Maharani; I G. B. Wahyu Nugraha Putra; Benny Benny (Riviera Publishing, 2022)
This article is entitled The Analysis of Abstraction Personification in Skillet’s Selected Song. The aim of this study is to find and analyse the abstraction personification and the meaning inside the selected song created by Skillet. This study uses the theory of personification from Zhu (1991) and the theory of meaning from Leech (1981) to find out and classify the data in the lyric taken from the selected song, such as: Terrify the Dark, Vapor, and Stars. This study uses library method and qualitative method in collecting and analysing the data. After collecting and analysing the data, it has been found that there are ten lyrics that contain abstraction personification in this study, this study shows that there is abstraction personification based on the theory of Zhu (1991) present in the song selected, but there are only four types of meaning from seven types of meaning by Leech (1981) found inside, there are conceptual, connotative, affective, and thematic meaning.